Local Government Respond to COVID-19 Pandemics: A Study of South Tangerang City - Satispi, Evi; DyasTuti, Retnowati Wahyuning; Fathani, Aqil Teguh; Kaewhanam, Phimlikid (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to analyze local governments' efforts in promoting and implementing policies issued during COVID-19. It can also be seen what instruments are used by the government in the socialization of the policy, and the communication between local government officials and the media, society, and business can be seen. The method used in this research is descriptive with a qualitative approach to see the stages of communication in their role in socializing the Tangerang City Government's policies. The results showed that a policy's socialization had gone very well through various socialization of communications such as online media, print media, and electronic media. This type of socialization media is the main instrument of the Tangerang local government in disseminating policies. Another type of socialization is direct media or outreach to each village. It is recommended that the Tangerang City Government improve its performance in disseminating policies to achieve the resulting policy objectives to build public order towards the policies taken.